The big pivot radically practical strategies for a hotter, scarcer, and more open world - Winston, Andrew S. (Boston Harvard Business Review Press, 2014)
The evidence is all around us. Extreme weather, driven by climate change, is shattering records all over the planet. Our natural resources are in greater demand than ever before as a billion more people enter the global middle class, wanting more of everything. Radical transparency is opening up company operations and supply chains to public scrutiny.
Includes bibliographical references (pages 293-319) and index.
Keywords: Management--Environmental aspects